Application of Nursing Process and Its Affecting Factors among Nurses Working in Mekelle Zone Hospitals, Northern Ethiopia - Fisseha Hagos; Fessehaye Alemseged; Fikadu Balcha; Semarya Berhe; Alemseged Aregay (Nursing Research and Practice)
Background. Nursing process is considered as appropriate method to explain the nursing essence, its scientific bases, technologies and humanist assumptions that encourage critical thinking and creativity, and permits solving problems in professional practice. Objective. To assess the application of nursing process and it’s affecting factors in Mekelle Zone Hospitals. Methods. A cross sectional design employing quantitative and qualitative methods was conducted in Mekelle zone hospitals March 2011. Qualitative data was collected from14 head nurses of six hospitals and quantitative was collected from 200 nurses selected by simple random sampling technique from the six hospitals proportional to their size. SPSS version 16.1 and thematic analysis was used for quantitative and qualitative data respectively. Results. Majority 180 (90%) of the respondents have poor knowledge and 99.5% of the respondents have a positive attitude towards the nursing process. All of the respondents said that they did not use the nursing process during provision of care to their patients at the time of the study. Majority (75%) of the respondent said that the nurse to patient ratio was not optimal to apply the nursing process. Conclusion and Recommendation. The nursing process is not yet applied in all of the six hospitals. The finding revealed that the knowledge of nurses on the nursing process is not adequate to put it in to practice and high patient nurse ratio affects its application. The studied hospitals should consider the application of the nursing process critically by motivating nurses and monitor and evaluate its progress.